Neuroradiological Features of Six Patients with Propionic Acidemia - Berenguer-Potenciano, Maria; Víllora-Morcillo, Nuria; Quijada-Fraile, Pilar; Martín-Hernández, Elena; Camacho-Salas, Ana; García-Silva, Maria Teresa; Martinez De Aragón, Ana (Journal of Pediatric Neurology, 2018)
Propionic acidemia (PA) is a rare autosomal recessive neurometabolic disorder caused by propionyl-CoA carboxylase deficiency. Diffuse brain atrophy, myelination delay, and basal ganglia abnormalities, either chronic or transient, have been previously reported in brain magnetic resonance imaging (MRI) of patients with PA. Clinical manifestations are heterogeneous and long-term outcome of affected individuals is unpredictable.Neuroradiological studies and clinical symptoms of six patients diagnosed with PA were reported in our center between 1999 and 2015. Brain MRI was performed in all patients (sagittal T1-weighted images, axial T2-weighted images, coronal FLAIR images, and axial diffusion-weighted images) and magnetic resonance spectroscopy (MRS) in four of them. Follow-up MRI abnormalities are heterogeneous and highly variable over time, in some cases even reversible. New neuroradiological findings are for the first time reported here as cerebellum signal changes, posterior brain stem diffusion restriction, and cortical development malformations. We suggest including serial MRI in follow-up programs as a monitoring tool in assessing intracerebral changes in PA, but more data are required to evaluate the benefits of serial MRI in PA patients.
Keywords: propionic acidemia; neurometabolic disorder; neuroradiological findings; magnetic resonance imaging; magnetic resonance spectroscopy